Neglected Human Risk Factors Determining Sustainable Health by Microbial Causes: Individual Versus Social Conducts, Scientific Versus Stultified Behaviour - Fernando Baquero (Microbial Biotechnology)
ABSTRACT Microbes constitute a ubiquitous warp, a highly sensitive skin of the biosphere that can be scratched and damaged by all human activities. However, the existence of life in general and the human species, in particular, depends on the intelligent preservation of such a biological microbiological cement linking our health with the health of Earth. We are responsible for maintaining sustainable health by managing our damaging individual and social behaviour, and we are also charged with the duty of correcting the microbial disequilibrium we are provoking. The harmful secondary effects resulting from the nature of the species Homo sapiens are frequently neglected. However, sustainable health by microbial causes depends on our individual and social psychology. The role of individual psychology, social behaviour (including the ‘tragedy of the commons’), based on collective psychology, culture, values and social norms, and the influence on sustainable health of the methodology of research and management of interventions are briefly analysed. As a general antidote to our unavoidable natural stultified behaviour, education in science is the only possibility to counteract mistakes and restore human dignity.